Consequences of the SARS-COV-2 pandemic on Pediatric Emergency Services in Uruguay (Archives of Pediatrics of Uruguay, 2022)
In March 2020 the first case of coronavirus disease was confirmed in Uruguay, and lockdown was recommended. Health care services were reduced to Urgency and Emergency Services (ES).Objectives: to analyze the epidemiological characteristics of pediatric visits to the ES of the public and private subsector in Uruguay, during the first 4 months of the SARS-CoV-2 pandemic.Methods: descriptive, retrospective.Results: 23 institutions participated. 2 periods were considered: 1) pre-pandemic, 03/14/19 to 07/29/19, 2) 03/14/20 to 07/29/20. Visits: period 1: n=121,116 (< 15 years), period 2: n=33.099 (73% decrease). Hospital admissions: period 1: n=6,649 (rate 5.5). Period 2: n=2.948 (rate 9,5). Diagnoses period 1: High acute respiratory infection 39,892 (33%), low acute respiratory infection 8,656 (7%), minor trauma 8,651 (7%), gastroenteritis 8,044 (6,6%), asthmatic crisis/CBO 7.974 (6,5%), injuries 4,389 (3,6%), abdominal pain (3,528) 3%, mental health problems 859 (0.7%), seizures 758 (0.7%), social pathology 678 (0.5% ). 2020 diagnoses: high acute respiratory infection 5.168 (16%), minor trauma 2,759 (8%), injuries 2,652 (8%), abdominal pain 1,494 (4.5%), gastroenteritis 1,296 (4%), asthma/CBO 1,095 (3,3%), low acute respiratory infection 700 (2,1%), social pathology 522 (1,6%), mental health problems 471 (1,4%), seizures 408 (1,2%).Conclusions: in the first months of the pandemic there was a sustained and significant reduction in pediatric consultations in ES. There was no increase in absolute frequency of any of the diagnoses. There was a historical decrease in low respiratory infections and hospitalizations due to this cause in the whole country. Maintaining a surveillance of the visits in the ES would enable practitioners to identify and take action in case of changes or previously undetected risk situations.
Keywords: COVID-19; Pandemics; Emergency medical service; Pediatrics